1999
DOI: 10.1104/pp.120.4.961
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of a Secreted Soluble Protein to the Vacuole via a Membrane Anchor1

Abstract: To further understand how membrane proteins are sorted in the secretory system, we devised a strategy that involves the expression of a membrane-anchored yeast invertase in transgenic plants. The construct consisted of a signal peptide followed by the coding region of yeast invertase and the transmembrane domain and cytoplasmic tail of calnexin. The substitution of a lysine near the C terminus of calnexin with a glutamic acid residue ensured progression through the secretory system rather than retention in or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 50 publications
4
35
1
1
Order By: Relevance
“…This is in agreement with all previous reports (Barrieu and Chrispeels, 1999;Benghezal et al, 2000;Brandizzi et al, 2002;daSilva et al, 2006).…”
Section: The Drag-and-drop Assay Reveals Receptor Transit Via the Pm supporting
confidence: 83%
See 1 more Smart Citation
“…This is in agreement with all previous reports (Barrieu and Chrispeels, 1999;Benghezal et al, 2000;Brandizzi et al, 2002;daSilva et al, 2006).…”
Section: The Drag-and-drop Assay Reveals Receptor Transit Via the Pm supporting
confidence: 83%
“…Earlier studies pointed either to the PM (Benghezal et al, 2000) or the tonoplast (Barrieu and Chrispeels, 1999) as the default location. In yeast, removal of the cytosolic tail of the VSR (VPS10) results in accelerated degradation in the vacuole (Cereghino et al, 1995;Cooper and Stevens, 1996).…”
Section: Where Is the Default Location For Type 1 Membrane-spanning Pmentioning
confidence: 99%
“…The problem of these approaches is that the location of the membrane protein itself is not addressed directly by analyzing the location of membrane-bound reporters. Instead, conclusions are suggested indirectly from the location of a soluble reporter released from the membrane chimera.As proposed by Barrieu and Chrispeels (1999), it is possible that, while reaching a lytic compartment on its way to its default destination, a chimeric membrane protein releases its reporter. The released soluble protein then can be transported farther down the secretory pathway while the membrane portion remains in a different location.…”
mentioning
confidence: 99%
“…This hypothesis was further tested with type I membrane-spanning reporter fusions constructed from ER residents and mutagenesis of the known ER retention signals. One of these studies confirmed the tonoplast as default (Barrieu and Chrispeels, 1999), whereas the other suggested the PM (Benghezal et al, 2000).…”
Section: Transport Of Membrane Proteinsmentioning
confidence: 65%
“…The problem with many of these studies is that the reporter fusion is proteolytically cleaved and leads to the detection of the soluble reporter in either the vacuole (Barrieu and Chrispeels, 1999;Langhans et al, 2008) or the extracellular medium (Benghezal et al, 2000). Depending on the position in the secretory pathway, cleavage can either lead to secretion from the Golgi or vacuolar transport from the PVC, but it would be ideal to have a reporter that is stable.…”
Section: Transport Of Membrane Proteinsmentioning
confidence: 99%